A Redox Hydrogel Protects the O2‐Sensitive [FeFe]‐Hydrogenase from Chlamydomonas reinhardtii from Oxidative Damage1. Issue 42 (12th June 2015) - Oughli, Alaa Alsheikh; Conzuelo, Felipe; Winkler, Martin; Happe, Thomas; Lubitz, Wolfgang; Schuhmann, Wolfgang; Rüdiger, Olaf; Plumeré, Nicolas
Abstract The integration of sensitive catalysts in redox matrices opens up the possibility for their protection from deactivating molecules such as O2. [FeFe]‐hydrogenases are enzymes catalyzing H2 oxidation/production which are irreversibly deactivated by O2. Therefore, their use under aerobic conditions has never been achieved. Integration of such hydrogenases in viologen‐modified hydrogel films allows the enzyme to maintain catalytic current for H2 oxidation in the presence of O2, demonstrating a protection mechanism independent of reactivation processes. Within the hydrogel, electrons from the hydrogenase‐catalyzed H2 oxidation are shuttled to the hydrogel–solution interface for O2 reduction. Hence, the harmful O2 molecules do not reach the hydrogenase. We illustrate the potential applications of this protection concept with a biofuel cell under H2/O2 mixed feed.